Morphological and molecular characterization of Colletotrichum nymphaeae and C. fructicola associated with anthracnose symptoms of grape in Santa Catarina State, southern Brazil - Guginski-Piva C.A.* (2018)
© 2018, Deutsche Phytomedizinische Gesellschaft.Recent review described that grape anthracnose in Brazil is caused by Elsinoe ampelina. However, in many countries, anthracnose can be associated with different species of Colletotrichum. A group of 20 isolates obtained from leaves and shoots of grapes genotypes showing typical anthracnose symptoms were characterized using morphological criteria, species-specific PCR and internal transcribed spacer (ITS) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) sequencing. Two morphological types (I and II) were identified on the basis of colony appearance and conidial shape. Type I (Colletotrichum acutatum complex) produced colonies of flat growth salmon concentric rings and short cylindrical conidia measuring 13 × 5.73 µm. Type II (C. gloeosporioides complex) produced cotton growth white colonies and cylindrical conidia with both ends rounded and the same size as in type I. Phylogenetic trees based on Bayesian inference and using combined ITS and GAPDH sequence alignment exhibited five main clades, which represented the species of C. acutatum (C. nymphaeae) and C. gloeosporioides (C. fructicola) complexes. The standard isolates of type I CB-a (C. nymphaeae) and type II CB-g (C. fructicola) were pathogenic to potted vines of the Niagara cultivar 1 week after inoculation. This is the first report of the occurrence of C. nymphaeae and C. fructicola associated with grape anthracnose symptoms in Santa Catarina State, southern Brazil.